Percentiles of body mass index and waist circumference for Costa Rican children and adolescents - Núñez Rivas, Hilda Patricia (2022)
Introduction: body mass index (BMI) and waist circumference (WC) are anthropometric indicators used to define overweight/obesity and to predict the risk of cardiovascular disease, respectively, in adolescents and children. Objectives: to describe and provide estimations of BMI and WC distribution according to percentiles in a sample of Costa Rican students, and to test group differences at the 50th percentile with the international references by the National Center for Health Statistics of the United States of America in 2012, 2016 and 2021. Material and methods: a cross-sectional and descriptive study was carried out with 2.684 students from 7 to 17 years of age in 64 educational centers of Costa Rica. The weight of the students was determined with a Tanita model SC-331 S, and height was measured with a SECA stadiometer, model 217, to estimate BMI. To determine abdominal circumference a measuring tape was used. All procedures were approved by the INCIENSA Scientific Ethics Committee. The statistical analysis of the data was made with the SPSS 22,0 package. Results: the first percentile distribution of BMI and WC is provided. According to BMI, 16,3 % of the student population had obesity and 26,2 % had overweight. WC values increased over the years and some significant differences were found between genders. The BMI and WC curves of Costa Rican children showed patterns similar to the three international references they were compared to. Conclusions: obesity has become the main nutritional problem in Costa Rica. The BMI and WC trend graphs proposed in this study are a useful public health tool to monitor the overweight/obesity epidemic.